Criminalistics characteristics of arms trafficking offences committed by organised groups and criminal organisations (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The article identifies which criminal offences fall into the category of those related to illicit arms trafficking and are the most common in the recorded proportion of criminal offences committed by organised groups and criminal organisations. These include, in particular, criminal offences under Articles 201, 262, 263, 263-1, 264, 410, 411 of the Criminal Code of Ukraine. The author also emphasises the need to include here also those crimes provided for in Articles 269 and 440 of the Criminal Code of Ukraine, but given that they are not common in the recorded number of crimes and criminal offences, it is justified that it is inexpedient to study them in depth.The elements of the forensic characterisation of crimes in the field of illegal arms trafficking committed by organised groups and criminal organisations which have significant forensic significance include: the method of committing the crime, the object of the crime, the circumstances of the crime (including the situation at the scene), traces, characteristics of the leader and other members of the criminal association.It is established that the method of committing crimes in the field of firearms trafficking involving organised groups and criminal organisations is a full-structured one. It is also found that in most cases it includes actions of preparation, direct commission and concealment. Moreover, it is determined that the setting of these crimes includes information about the place and time of preparation for the commission of a criminal offence, as well as the setting of the place of commission and concealment. However, it is emphasised that the trace picture is not always characterised by a significant number of material traces, but it is characterised mainly by ideal traces-reflections preserved in people's memory. With regard to the characteristics of the personalities of criminal groups, the author emphasises that this issue is quite complex and therefore requires further research.